LEVEL UP SKILL RIAS WAJAH GERIATRI MENGGUNAKAN MODEL PEMBELAJARANPROJECT BASED LEARNING (PjBL) - Nabila Tri Afifah; Arrori Ashar Hidayad (Prosiding Seminar Nasional Indonesia, 2025)
Researchers made initial observations of students' abilities regarding facial makeup. Problems were found in geriatric makeup materials. This is due to the boring learning model and the learning strategies applied by the teacher, which limit students from exploring their knowledge, while an effective learning environment can increase student competency. The goal of this investigation was to ensure: (1) implementation of syntax; (2) improvement of students' competence in doing geriatric makeup; and (3) student responses to the PjBL learning model. In this study, classroom action research (CAR) of this kind was employed, and the participants were 26 students from SMK Negeri 3 Kediri. The results showed: (1) The implementation of the syntax of the PjBL learning model from cycle I to cycle II had been corrected appropriately so that there was an increase in mark. (2) The success rate on cognitive learning outcomes tests increased from 69.23% to 96.15%; the success rate on performance tests increased from 84.61% to 96.15%; the percentage of students' attitude scores with good and very good predicates were initially 88, 46%, and 11.54%; the numbers increased to 42.31% and 57.69%. (3) The percentage of students' responses to the predicate of very good and good was initially 31% and 31% of 26 students, but the number increased to 54% and 35% of 26 students. The percentage in the sufficient category decreased from 19% to 11%.